(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
The lexical level of stylistic analysis focuses on the study of vocabulary and its stylistic functions in different types of texts. Words are not only carriers of meaning but also reflect social, emotional, and contextual nuances. This article examines the classification of lexical layers, including neutral, literary, and colloquial vocabulary, as well as stylistically coloured groups such as archaic words, neologisms, slang, jargon, and professional terminology. The study highlights how lexical choices influence tone, register, and expressiveness in communication. Furthermore, it explores the role of vocabulary in conveying cultural and social identity, emphasizing the importance of lexical analysis in stylistics and related linguistic disciplines.